ANALYSIS OF EXPORTS OF FIVE MAIN FISHERY PRODUCT COMMODITIES IN BATAM CITY USING THE MARKOV CHAIN MODEL - Anggraeni, Andini Setyo; Sabarinsyah, Sabarinsyah; Aprilla Handayani, Vitri; Tarsila, Huiliana (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Indonesia, an archipelagic country, boasts significant potential in the fisheries sector, notably in the export of fishery products. Batam as a free trade zone plays a major role in Indonesia's fishery product exports. According to the Central Statistics Agency's data, there has been a 2.47% decline in fish and shrimp exports in January and February 2023 compared to January 2022. Therefore, further analysis is needed on projected exports of fishery products in Batam. This study focuses on the utilization of the Markov chain model to analyze the export dynamics of Batam City's primary fishery product commodities, including Seaweed, Fish, Shrimp, Crab, and Shellfish. Monthly export data for Batam City's fishery products throughout 2021-2023 sourced from The Ministry of Marine Affairs and Fisheries. Based on these data, the transition probability matrix will be calculated based on the number of export transitions below and above the Moving Average (MA 12) value. The Markov chain model for this case is an erdogic Markov chain model, in order that the limiting probability of the Markov chain model can be determined. The result shows that exports of fish, shrimp and crab in the long term will exceed the average export size in the past year each after 7 months, 11 months, and 14 months later respectively, while exports of seaweed and shellfish in the long term will be below the large average exports in the past year after 15 and 5 months. This research result offer valuable insights for the government to formulate strategies and policies concerning fishery product exports